(untitled) (Global Journal of Human-Social Science, 2016)
An attempt has been done on attitude towards sexual harassment which is critical issue nowadays in higher institutions The result of the study could suggest for putting proper polices in place which considered as vital in preventing sexual harassment as well as creating awareness about sexual harassment issue specially in higher institutions as well as other sectors in general For study purpose we focus to investigate attitude towards on sexual harassment of students in Wolaita Sodo University students taking a sample of 377 students from all batch admitted in Wolaita Sodo University Self-administered questionnaire was developed and piloted for use in this study The cross tabulation with Chi-square test and binary logistic regression were employed to analyze the data The result of cross tabulation with Chi-square test show that sex and level of schooling have significantly associated with attitude towards on sexual harassment at 5 level of significance Also the result of the binary logistic regression analysis showed that age sex and level of schooling have a significant relation with attitude towards on sexual harassment at 5 level of significance It can be concluded that to promote and improve students attitude towards on sexual harassment some crucial steps regarding gender issue in counseling as well as guiding about sexual harassment should be taken into consideration